Mortality from Crohn's disease in Leicestershire, 1972-1989: an epidemiological community based study. Issue 9 (September 1992) - Probert, C S; Jayanthi, V; Wicks, A C; Mayberry, J F
Abstract : Mortality among 610 people with Crohn's disease identified in a population based study from 1972-89 was assessed. In Europeans the overall mortality was not increased, the standardised mortality ratio (SMR) was 71.8 (95% confidence interval (CI) 49 to 101). The SMR in South Asians was 0, (95% CI 0 to 1590). The SMR varied with the site of disease (chi 2 (4) = 10.5, p < 0.05) and was highest in those with duodenal and jejunal involvement (SMR = 210, 95% CI 44 to 621). Survival curve comparisons showed that colonic disease carried a worse prognosis than terminal ileal disease (chi-2 = 9, p < 0.01) or mixed site disease (chi-2 = 4.7, p < 0.05). Mortality was particularly high during the first six years. It was increased in patients who had undergone more than one resection (SMR = 137, 95% CI 28 to 401) or an ileoanal anastomosis (SMR = 357, 95% CI 9 to 1070), although no difference was significant. Mortality did not change significantly during the study. Such information needs to be made available, not just to patients, their families, and their doctors, but perhaps more importantly, to actuaries, insurers, and those advising employers.